Contening cultures amongst development actors - Messerschmidt, Don; Gurung, Barun; Biggs, Stephen D. (International Development Research Centre, 2004)
Lewis et al (2003) establish a cogent argument which suggests that serious analysis of the culture of aid organizations, and of the relationships with other actors, matters, and that it is a neglected area of analysis. Their discussion raises important new questions about the development enterprise from an internal perspective that heretofore has been neglected or ignored. Contrasting the article by Lewis et al. with a book by Harrison and Huntington (2000) reinforces that conviction. Throughout the Harrison and Huntington book-- whose authors provide an excellent overview of the history of the study of culture as something that certainly does ‘matter’ in development--we kept saying to ourselves that ‘All this is fine, but it is focussed (as is much of the ancillary literature on ‘culture’ in development) on looking outward, at others undergoing development, without consideration of the development agency actors themselves. It mostly addresses questions and issues concerning the question: Why some political and national systems succeed and others fail.